Mobility biographies: Elements of a biographical theory of travel demand - Scheiner, Joachim (ERDKUNDE, 2007)
The contribution presents theoretical considerations and an overview on empirical knowledge from a research field recently emerging in transportation research, in which transport geographers play a prominent role. This research field deals with the development of travel demand over the life course of individuals. This process is referred to as ‘mobility biographies’. It is embedded into the context of other ‘partial biographies’, namely residential biography, employment biography, and household biography. The hypothesis is that travel demand on an individual level is relatively stable in the medium term, but changes significantly in the context of certain key events in the life course. Such key events include, among others, residential location changes, workplace changes, and the birth of children. The paper concludes with some methodological considerations and the identification of research requirements.